Catalytic Asymmetric Organozinc Additions to Carbonyl Compounds - Pu, Lin; Yu, Hong-Bin (Chemical reviews, 2001)
Because of the tremendous effort of a great number of researchers, the catalytic asymmetric dialkylzinc addition to aldehydes has become a mature method. Ligands of diverse structures have been obtained, and high enantioselectivity for all different types of aldehydes have been achieved. Among the representative excellent catalysts are compounds 1, 8, 120, 325, 352, and 360 discussed above. However, compared to the well-developed dialkylzinc addition, the catalytic asymmetric reactions of aryl-, vinyl-, and alkynylzinc reagents with aldehydes are still very much under developed. Although catalysts such as (S)-402 and 210 prepared by Pu and Bolm have shown good enantioselectivity for the reaction of diphenylzinc with certain aromatic and aliphatic aldehydes, the generality of these catalysts for other [formula: see text] arylzinc reagents have not been studied. The vinylzinc additions using ligands 1 and 412 reported by Oppolzer and Wipf were highly enantioselective for certain aromatic aldehydes but not as good for aliphatic aldehydes. Carreira discovered highly enantioselective alkynylzinc additions to aldehydes promoted by the chiral amino alcohol 415, but this process was not catalytic yet. Ishizaki achieved good enantioselectivity for the catalytic alkynylzinc addition to certain aldehydes by using compounds 160, but the enantioselectivity for simple linear aliphatic aldehydes was low. Another much less explored area is the organozinc addition to ketones. Yus and Fu showed very promising results by using ligands 381 and 406 for both dialkylzinc and diphenylzinc additions to ketones, but the scope of these reactions were still very limited. Therefore, more work is needed for the aryl-, vinyl-, and alkynylzinc additions and for the organozinc addition to ketones, although many good catalysts have been obtained for the dialkylzinc addition to aldehydes. Development of these reactions will allow the catalytic asymmetric synthesis of a great variety of functional chiral alcohols that are either the structural units or synthons of many important organic molecules as well as molecules of biological functions. Macromolecular chiral catalysts have become a very attractive research subject in recent years because these materials offer the advantages of simplified product isolation, easy recovery of the generally quite expensive chiral catalysts, and potential use for continuous production. Three types of macromolecules including flexible achiral polymers anchored with chiral catalysts, rigid and sterically regular main chain chiral polymers, and chiral dendrimers have been used for the asymmetric organozinc addition to aldehydes. Among these materials, the binaphthyl-based polymers such as (R)-451 developed by Pu have shown very high and general enantioselectivity. Study of the binaphthyl polymers in the asymmetric organozinc addition has demonstrated that it is possible to systematically modify the structure and function of the rigid and sterically regular polymer for the development of highly enantioselective polymer catalysts. The catalytic properties of highly enantioselective monomer catalysts can also be preserved in the rigid and sterically regular polymer provided the catalytically active species of the monomer catalyst is not its aggregate. The TADDOL-based polymers and dendrimers prepared by Seebach showed very high and stable enantioselectivity for the diethylzinc addition to benzaldehyde even after many cycles. These studies on macromolecular chiral catalysts demonstrate that these materials are potentially very useful for practical applications.